Acellular nerve graft enriched with mesenchymal stem cells in the transfer of the phrenic nerve to the musculocutaneous nerve in a C5‐C6 brachial plexus avulsion in a rat model. Issue 1 (18th October 2021) - González Rodríguez, Alba; González Porto, Sara A.; Comellas Melero, Nerea; Arufe, María C.
Abstract: Introduction: Phrenic nerve transfer has been shown to achieve good nerve regeneration in brachial plexus avulsion. Acellular nerve allografts (ANAs) showed inferior results to autografts, which is why its use with mesenchymal stem cells (MSCs) is currently being studied. The aim is to study the effect of BM‐MSCs associated with ANAs in a rat model of phrenic nerve transfer to the musculocutaneous nerve in a C5‐C6 avulsion. Material and methods: 42 Wistar‐Lewis rats underwent a C5‐C6 lesion in the right forelimb by excising a 3 mm segment from both roots, followed by a phrenic nerve transfer to the musculocutaneous nerve associated with the interposition of a three types of nerve graft (randomly distributed): control (autograft) group (n = 12), ANAs group (n = 12), and ANAs + BM‐MSCs group (n = 18) After 12 weeks, amplitude and latency of the NAP and the compound motor action potential (CMAP) were measured. Biceps muscles were studied by histological analysis and nerve grafts by electron microscopy and fluorescence analysis. Results: Statistically significant reductions were found in latency of the CMAP between groups control (2.48 ± 0.47 ms) and experimental (ANAs: 4.38 ± 0.78 ms, ANAs + BM‐MSCs: 4.08 ± 0.85 ms) and increases in the amplitude of the CMAP between groups control (0.04388 ± 0.02 V) and ANAs + BM‐MSCs (0.02275 ± 0.02 V), as well as in the thickness of the myelin sheath between groups control (0.81 ± 0.07 μm) and experimental (ANAs: 0.72 ± 0.08 μm, ANAs + BM‐MSCs: 0.72 ± 0.07 μm) and in the area of the myelin sheath between groups control (13.09 ± 2.67 μm 2 ) and ANAs (10.01 ± 2.97 μm 2 ) ( p  < .05). No statistically significant differences have been found between groups ANAs and ANAs + BM‐MSCs. Conclusions: This study presents a model for the study of lesions of the upper trunk and validates the autologous graft as the gold standard.